Kinetics of Soluble Mediators of the Host Response in Ebola Virus Disease. (8th August 2018) - Kerber, Romy; Krumkamp, Ralf; Korva, Misa; Rieger, Toni; Wurr, Stephanie; Duraffour, Sophie; Oestereich, Lisa; Gabriel, Martin; Sissoko, Daouda; Anglaret, Xavier; Malvy, Denis; May, Jürgen; et al.
Abstract: Background: The pathophysiology of Ebola virus disease (EVD) is still poorly understood. This study aimed at identifying soluble biomarkers that inform on disease mechanisms. Methods: Fifty-four soluble mediators of the immune, coagulation, and endothelial system were measured in baseline and follow-up samples from hospitalized patients with EVD, using Luminex technology. Cross-sectional expression levels and changes over time were correlated with outcome. Results: Levels of circulating proinflammatory cytokines and chemokines, as well as markers of endothelial dysfunction and coagulopathy, were elevated on admission to hospital in patients who died from EVD as compared to survivors. These markers further increased in patients who died and/or decreased over time in survivors. In contrast, markers of gut integrity and T-cell response were higher in survivors and increased until discharge. Conclusions: Inflammatory response, endothelial integrity, gastric tissue protection, and T cell immunity play a role in EVD pathophysiology.